Design and development of an augmented reality adventure game with Unity3D - Hu, Shuyi (Nanyang Technological University, 2020)
The increasing popularity of Augmented Reality technology has gradually changed people’s way of life. More and more AR applications have come to the public view, such as AR classroom for education, Ikea AR for shopping, Pokemon Go for entertainment. As such, this project gives an attempt to design and implement an AR adventure game which has three game levels, for the students to explore more about the AR technology while exploring the campus. The adventure game, which integrating with AR scenes, is developed using Unity3D and AR Foundation. In the game, the player will start an adventurous journey with the main character, a freshman of EEE, John, to figure out what the mysterious power is affecting the school of EEE. On the movement of the game, the student will visit some important places around the school, and this could help to learn more around the campus. The project is a practice of Unity3D game development and AR application based on AR Foundation. In order to achieve the game functionalities and AR scene applications, the knowledge of programming languages, game design principles, AR technology are applied. The process of design and development is further explained in the report.